2009
DOI: 10.1163/156854108x398453
|View full text |Cite
|
Sign up to set email alerts
|

A survey of entomopathogenic nematodes of the families Steinernematidae and Heterorhabditidae (Nematoda: Rhabditida) in the north-west of Iran

Abstract: Summary - During 2002During -2004, a survey of entomopathogenic nematodes was conducted for the first time in Iran throughout the three provinces in the north-west of the country. Soil samples were tested for the presence of steinernematid and heterorhabditid nematodes by baiting with Galleria mellonella larvae. Of the 833 soil samples studied 27 were positive for entomopathogenic nematodes (3.2%), with 17 (2.0%) containing Heterorhabditis and ten (1.2%) Steinernema isolates. Morphological and molecular studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 46 publications
5
28
0
Order By: Relevance
“…This conforms many other reports that mobility and survival of EPN are favoured in soils with high sand content (Hazir et al, 2003;Kary et al, 2009). Most of the positive samples (89.65%) were from acidic soil.…”
Section: Discussionsupporting
confidence: 93%
“…This conforms many other reports that mobility and survival of EPN are favoured in soils with high sand content (Hazir et al, 2003;Kary et al, 2009). Most of the positive samples (89.65%) were from acidic soil.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the choice of sampling sites may contribute to differences in EPN recovery percentage . However, this low recovery percentage is not unusual, and it has already been reported from other surveys (Rosa et al, 2000;Hazir et al, 2003;Kary et al, 2009). Furthermore, the low H. bacteriophora recovery rate compared to Steinernema spp.…”
Section: Discussionsupporting
confidence: 78%
“…Based on the previous survey results (Susurluk, 2007), H. bacteriophora was firstly reported from the eastern part of Turkey. In a study conducted in northwestern Iran, which shares a border region with Turkey and has similar climatic conditions, Kary et al (2009) also found that H. bacteriophora was the most common species, followed by S. feltiae. The natural distributions of heterorhabditids and steinernematids are affected by climatic and geographical variations (Yoshida et al, 1998).…”
Section: Discussionmentioning
confidence: 93%
“…Second, only room temperature was used for baiting the soil samples during EPN isolation. Third, a high rate of chemical pesticides is being used to control pests in agricultural areas (Kary et al, 2009). Another reason may be the sample size.…”
Section: Discussionmentioning
confidence: 99%